Asymmetric Synthesis of Multi‐substituted Prolines via a Catalytic 1, 3‐Dipolar Cycloaddition Using a Monocationic ZnIIOAc Complex of a Chiral Bisamidine Ligand, Naph‐diPIM‐dioxo‐R. Issue 22 (4th September 2020) - Chaithanya Kiran, I. N.; Fujita, Kazuki; Tanaka, Shinji; Kitamura, Masato
Abstract: A monocationic zinc acetate complex of chiral bisamidine‐type bidentate ligand ( R )‐ or ( S )‐Naph‐diPIM‐dioxo‐ i Pr (L R or L S ) catalyzes a 1, 3‐dipolar cycloaddition between tridentate‐type imino esters and acrylates in the absence of an external base to give the corresponding multi‐substituted prolines with high reactivity, diastero‐/enantio‐/regio‐selectivity, productivity, and broad generality. An anionic acetate ligand of the Lewis acidic Zn complex acts as a Brønsted base to facilitate a smooth intramolecular deprotonation to generate an imino N, O ‐ cis ‐Zn enolate. The oxygen atoms of two dioxolanes of the L R /L S ligand form a C 2 chiral scaffold that coordinates the Zn enolate via a non‐bonding n‐π* interaction. This view is supported by the lack of enantioselectivity obtained with an sp 2 N‐based Ph‐BOX ligand that has no oxygen atom in the reaction site. Abstract : Zn‐catalyzed cycloaddition : A highly efficient catalytic asymmetric 1, 3‐dipolar cycloaddition was realized between tridentate α‐imino esters and acrylates to furnish various multi‐substituted prolines. A Brønsted base/Lewis acid synergistic effect of [Zn II OAc(L R or L S )] + (OTf) − facilitates an intramolecular deprotonation to generate an N, O ‐ cis ‐Zn enolate, which is attracted in the catalyst to the dioxo‐ i Pr side via an n‐π*C=N interaction to realize high selectivity.